Analysis of Health Services at Sukamerindu Community Health Center in Bengkulu City - Rinaldo, Rofi; Aminuddin, Achmad; Agus, Nourfarozi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study assesses the quality of health services at Sukamerindu Community Health Center in Bengkulu City, Indonesia, utilizing a descriptive qualitative research approach. Through observation, interviews, and documentation, the research examines five dimensions: Available & Sustainable, Reasonably Acceptable, Achievability, Easy to Reach, and Quality. While the health center effectively organizes services, achieves reasonable acceptability, and is easy to reach, challenges exist in guaranteeing service products and optimizing physical facilities. Overall, the health services at Sukamerindu Community Health Center fall short of community expectations. Addressing these gaps is essential for enhancing the health center's effectiveness and aligning services with community needs and preferences.